Gamifikasi dan Game-Based Learning dalam Pembelajaran Bahasa Arab: A Scoping Review - Julham Hukom (CV. SINAR HOWUHOWU, 2026)
Gamification and game-based learning (GBL) have emerged as innovative approaches in Arabic language education. However, comprehensive reviews mapping trends, platforms, and research outcomes in this field remain limited. This scoping review aims to map and analyze the literature addressing the use of gamification and GBL in Arabic language learning contexts. Searches were conducted across four databases (Scopus, Web of Science, Google Scholar, and ERIC) using structured search queries with keywords including gamification, game-based learning, serious game, educational game, and digital game, combined with Arabic language, teaching Arabic, Arabic learning, and Arabic literacy. The PRISMA-ScR framework was used as a reporting guideline. Of 247 articles initially identified, 20 studies met the inclusion criteria after screening. The review findings indicate that the most widely used gamification platforms are Kahoot!, Quizizz, Wordwall, and Duolingo. The majority of studies reported positive impacts on learners' motivation, engagement, and academic achievement, particularly in Arabic vocabulary and grammar acquisition. Studies were conducted across various educational levels, from primary school to higher education, with geographic contexts dominated by Malaysia and Indonesia. Nevertheless, research gaps remain regarding productive skills (speaking and writing), long-term effects of gamification, and the limited use of rigorous experimental designs. This scoping review provides a useful research map for researchers, educators, and educational technology developers in Arabic language instruction.